The role of public loans in improving economic activities: Jordan as a model - Al-Maaitah, Othman Zaal Faris (Journal of Economic, Administrative and Legal Sciences, 2022)
The importance of the study is due to addressing an important and necessary problem that developing countries are facing, including Iraq, Syria, Libya and Jordan, in order to benefit from external and internal borrowing as an important source of transferring economic activities in the state and its sectors, and the extent of its contribution to supporting the productive sectors, and in the effectiveness of borrowing in supporting economic development What is the role of loans in various areas of economic, social and political life, and what are the reasons that motivate the state to resort to borrowing. The importance of the study is clear that internal and external public loans have an important role in achieving the financial balance of the state, in addition to that they lead to achieving financial balance After the financial deficit, that the state was suffering from, and this is in order to cover unusual public Expenditures, and public loans do not represent it is a final resource for the state treasury, but the state Must return it along with paying the annual interest resulting from the loan. From the foregoing, the study reached conclusions, the most important of which was that public loans contribute to a large extent if directed to the desired goal in reviving and revitalizing the economies of countries that suffer from the problems of poverty, unemployment and lack of funding.